The Tradition of Ndarohi: Diversity of Punishments, Settlement of Fights in the Kute Pasekh Pekhmate Community from the Perspective of Islamic Criminal Law - M. Jakfar, Tarmizi; Yuhermansyah, Edi; Nurbaiti, Nurbaiti; Nazwa, Suha; Khairannur, Syarifah (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study analyzes the Ndarohi custom as a customary sanction imposed on the perpetrators of a fight. The Ndarohi custom is a tradition that has been passed down from generation to generation in the Kute Pasekh Pekhmate community, Lawe Alas District, Southeast Aceh Regency. The Kute Pasekh community believes that the Ndarohi custom is able to reunite the perpetrators of a fight as a family by imposing customary sanctions in the Ndarodi tradition. The focus of this study is how the traditional Kute Pasekh community maintains the Ndarohi custom in resolving fights amidst the strong current of modernization of criminal case resolution through litigation. The purpose of the study was to determine the practice of the Ndarohi custom in resolving fight cases, and to preserve the Ndarohi custom in the modern era. This study uses a qualitative descriptive method, data obtained through field interviews and literature. The results of the study show that sanctions for resolving disputes in fight cases are resolved according to the Ndrohi custom through a deliberation process. Then the party found guilty is charged with medical expenses for the victim and is given a sanction in the form of money and one goat, according to the decision from the results of the deliberation by Sakhak Bekhempat. Sanctions in the Ndarohi custom have various types according to the quality of the crime committed by the perpetrator. Fights that cause physical harm, not bleeding, are subject to the Nucupi custom sanction or the mbabe nakan sekhimah sope sekhanting sanction; all medical costs are borne by the perpetrator of the customary crime. While criminal acts of fighting that result in bleeding wounds are subject to the sanction of drawing error and a fine in accordance with the written customary provisions. The Kute Pasekh community still strongly adheres to the Ndarohi custom in resolving customary criminal disputes. In addition to being a hereditary tradition, it is also effective in uniting the relationship of the customary community to obtain eternal peace.